Ovarian cancer risk factors by tumor aggressiveness: An analysis from the Ovarian Cancer Cohort Consortium. Issue 1 (14th January 2019) - Fortner, Renée T.; Poole, Elizabeth M.; Wentzensen, Nicolas A.; Trabert, Britton; White, Emily; Arslan, Alan A.; Patel, Alpa V.; Setiawan, V. Wendy; Visvanathan, Kala; Weiderpass, Elisabete; Adami, Hans‐Olov; Black, Amanda; et al.
Abstract : Ovarian cancer risk factors differ by histotype; however, within subtype, there is substantial variability in outcomes. We hypothesized that risk factor profiles may influence tumor aggressiveness, defined by time between diagnosis and death, independent of histology. Among 1.3 million women from 21 prospective cohorts, 4, 584 invasive epithelial ovarian cancers were identified and classified as highly aggressive (death in <1 year, n = 864), very aggressive (death in 1 to < 3 years, n = 1, 390), moderately aggressive (death in 3 to < 5 years, n = 639), and less aggressive (lived 5+ years, n = 1, 691). Using competing risks Cox proportional hazards regression, we assessed heterogeneity of associations by tumor aggressiveness for all cases and among serous and endometrioid/clear cell tumors. Associations between parity (phet = 0.01), family history of ovarian cancer (phet = 0.02), body mass index (BMI; phet ≤ 0.04) and smoking (phet < 0.01) and ovarian cancer risk differed by aggressiveness. A first/single pregnancy, relative to nulliparity, was inversely associated with highly aggressive disease (HR: 0.72; 95% CI [0.58–0.88]), no association was observed for subsequent pregnancies (per pregnancy, 0.97 [0.92–1.02]). In contrast, first and subsequent pregnancies were similarly associated with less aggressive disease (0.87 for both). Family history of ovarian cancer was only associated with risk of less aggressive disease (1.94 [1.47–2.55]). High BMI (≥35 vs . 20 to < 25 kg/m 2, 1.93 [1.46–2.56] and current smoking ( vs . never, 1.30 [1.07–1.57]) were associated with increased risk of highly aggressive disease. Results were similar within histotypes. Ovarian cancer risk factors may be directly associated with subtypes defined by tumor aggressiveness, rather than through differential effects on histology. Studies to assess biological pathways are warranted. Abstract : What's new? In ovarian cancer, risk factor profiles may be associated with disease subtypes defined by aggressiveness independent of histology, according to this new analysis. In this large consortium‐based prospective study, the authors classified ovarian tumors according to aggressiveness, based on years between diagnosis and death. They hypothesized that pre‐diagnosis exposure to risk factors, such as smoking, BMI, family history, and pregnancy, would influence whether an ovarian cancer developed on a path toward more aggressive or less aggressive disease. Indeed, in clustering analysis, risk factor associations tracked by tumor aggressiveness rather than histotypes. Smoking and BMI, two modifiable risk factors, were associated with highly aggressive disease.